Speaking English through Good Morning Ball Game: A game for young learners - Weni Rahayu; Rima Andriani Sari (Universitas Negeri Padang, 2012)
Now English is introduced in elementary school as a local content. Teaching English to elementary school students is not easy because they easily get bored in learning. So, elementary school teacher should be able to find an appropriate way to motivate the students to learn English. One of the appropriate ways to activate elementary school students to speak English is by using a game known as “Good Morning Ball Game”. In this game, the teacher provides three different balls with a sentence will be said by the students. This game can activate the students’ willingness to study. So, the elementary school students do not easily get bored in learning English. AbstrakSekarang bahasa Inggris telah diajarkan di sekolah dasar sebagai salah satu pelajaran muatan lokal. Pengajaran bahasa Inggris di sekolah dasar ini tidaklah mudah karena siswa sekolah dasar cenderung mudah bosan dalam belajar. Untuk itu, guru harus dapat menggunakan cara yang tepat agar siswa dapat termotivasi untuk belajar bahasa Inggris. Salah satu cara yang cocok untuk mengaktifkan siswa sekolah dasar untuk berbicara bahasa Inggris adalah dengan menggunakan sebuah permainan yang dikenal dengan “Good Morning Ball Game”. Pada permainan ini guru menggunakan tiga buah bola yang berbeda sesuai dengan kalimat yang akan diucapkan siswa. Permainan ini dapat mengaktifasikan keinginan siswa untuk belajar. Jadi, siswa sekolah dasar tidak mudah bosan dalam belajar bahasa Inggris. Keywords (phrases)/Kata kunci: games, speaking, young learners, English